The Influence of Parental Attachment on Early Adolescents' Emotion Regulation in Junior High School Students - Eko Naning Wahyuningrum; Melly Latifah; Ujang Sumarwan (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
Emotion regulation is one of the developmental capacities early adolescents are expected to consolidate as biological, cognitive, and socioemotional shifts unfold. The family setting, particularly the affective bond with parents, has long been treated as a foundational source of this capacity, although the relative weight of mother-child and father-child attachment for adolescent emotion regulation remains debated. This article reports a study of 184 grade VIII students (78 boys, 106 girls) recruited from four junior high schools in Depok, West Java, who completed the Inventory of Parent and Peer Attachment and the Emotion Regulation Questionnaire. Because the indicators used were dimension-level composite scores rather than raw items, the measurement model was specified as formative, and the structural model was estimated through partial least squares structural equation modeling using SmartPLS 4. A permutation-based multi-group analysis (5,000 permutations) was used to test gender as a grouping variable. Mother-child attachment was a positive and significant predictor of emotion regulation (β = 0.382; t = 4.328; p < 0.001), whereas father-child attachment showed a positive direction but did not reach the 5 percent threshold (β = 0.163; t = 1.864; p = 0.062). The two predictors jointly explained 25.2 percent of the variance in emotion regulation. The permutation test yielded no significant gender difference, although the gap in the mother-child path coefficient between boys and girls was very close to the conventional cut-off and should be interpreted cautiously. Results point to the everyday emotional bond with the mother as the more salient correlate of early adolescents' emotion regulation, while leaving room for father-child attachment as a conceptually relevant resource that warrants further investigation in larger and more diverse samples